Watching the watchman from Ghana: The case of agenda 2063 - Isaac Addai (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
The Agenda 2063 framework document is the basis for Africa’s long term socio-economic and integrative transformation. It has a list of 12 flagship projects and programs that have to be implemented within the first ten year period of 2014 - 2023. The paper explores the correlation between the awareness of Ghanaians and the monitoring of the African Union Commission Agenda 2063 first ten-year flagship programs and projects and established a negative product-moment linear correlation coefficient which statistically established that Ghanaians are not aware of and do not monitor the Agenda2063 first ten-year flagship programs and projects.